The Association of Medicaid expansion with prescription drug utilization and expenditure among low-income participants with asthma - Shi, Lu; Li, Tao; Luck, Jeff; Ghanem, Buthainah (The Journal of asthma, 2023)
This study estimated the association between the 2014 Medicaid expansion and asthma-related prescription drug utilization and expenditures among low-income adult participants with asthma, including those with uncontrolled asthma, in the United States. In this national analysis, using a pooled dataset from 2007-2018 Medical Expenditure Panel Surveys (MEPS), regression discontinuity (D-RD) analyses estimated the association between Medicaid expansion and utilization of and expenditures for asthma-related prescription drugs among participants with asthma aged 26-64 with incomes below vs. at/above 138% of the federal poverty level (FPL). A sub-sample analysis was also conducted among participants with uncontrolled asthma. Utilization and expenditure outcomes were estimated using two-part models with logit as the first part and generalized linear models as the second part. Utilization of and total cost for asthma-related prescription drugs increased by 1.89 fills (p < 0.001) and $306.59 (p < 0.001) among participants with asthma with income below 138% FPL after Medicaid expansion. The utilization and total cost of both short-acting bronchodilators and inhaled corticosteroids (ICSs) increased after Medicaid expansion among participants with asthma with incomes below 138% FPL. Among participants with uncontrolled asthma with incomes below 138% FPL, utilization and expenditures increased after Medicaid expansion for all asthma-related prescription drugs and short-acting bronchodilators. Medicaid expansion was associated with increased utilization of and total expenditures for both quick-relief and preventive asthma medications among all low-income participants with asthma, but not with utilization of preventive medications among those with uncontrolled asthma.